A castelogia portuguesa e a evolução dos estudos sobre fortificações medievais em Portugal - Santos, Joaquim Rodrigues dos (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This text analyses the castelology produced over the times in Portugal, which reflects several different views relating to the medieval fortifications. Therefore, the castelologic studies published in Portugal are contextualized with the Portuguese historiography at different levels (artistic, military, economic, sociocultural, etc.), being also compared briefly with what happened in other countries.